Studi Litearatur: Kearifan Lokal Masyarakat Using sebagai Sumber Belajar IPS di Sekolah Dasar - Putri Rachmadyanti (Graduate School of Universitas Negeri Malang, 2021)
Abstract: Globalization has positive and negative impacts on human survival and culture. The positive impact discusses the role of advances in science and technology to make it easier for humans to solve problems, related to information literacy. The negative impact is related to the ease with which students are influenced by a culture that is not in accordance with the personality and character of the nation. Local wisdom-based education has an important role in internalizing the nation's values and culture. Social Studies as an integrated subject in elementary schools, accommodates material about the socio-cultural diversity of the local community. The Using community in Banyuwangi, East Java has a tourist village that supports cultural preservation, but the reality on the ground shows that teachers still do not have enough information about local wisdom. The purpose of the study was to describe the local wisdom of the Using Community as a source of social studies learning in elementary schools. The method in this research is literature study, by reviewing international and national journals about the local wisdom of the Using community in the last 10 years. The results show that the local wisdom of the Using community that can be used as a source of social studies learning and is relevant to the 2013 curriculum in elementary schools is the local wisdom of water conservation, agriculture, traditional houses, traditional ceremonies, and arts. The Using community upholds the customs that have been passed down from generation to generation. This local wisdom can be integrated into social studies learning in elementary schools at the high grade level.Abstrak: Globalisasi memberikan dampak positif dan negatif bagi kelangsungan hidup dan budaya manusia. Dampak postif membahas tentang peran kemajuan Ilmu Pengetahuan dan teknologi memudahkan manusia dalam meneyelesaikan masalah, berkaitan dengan literasi informasi. Dampak negatif berkaitan dengan mudahnya siswa terpengaruhi budaya yang kurang sesuai dengan kepribadian dan karakter bangsa. Pendidikan berbasis keraifan local memiliki peran penting dalam menginternalisasikan nilai dna budyaa bangsa. IPS sebagai matapelajaran yang terintegrasi di Sekolah dasar, mengakomodir materi tentang keragaman social budaya masyarakat setempat. Masyarakat Using di Banyuwangi Jawa Timur memiliki desa wisata yang mendukung pelestarian budaya, namun kenyataan di lapangan menunjukkan bahwa guru masih belum memiliki cukup informasi tentang kearifan lokal setempat. Tujuan penelitian adalah mendeskripsikan kearifan lokal Masyarakat Using sebagai sumber belajar IPS di Sekolah Dasar. Metode dalam penelitian ini adalah studi literatur, dengan mengkaji jurnal Internasional dan nasional tetang kearifan lokal masyarakat Using dalam 10 tahun terakhir. Hasil penelitian menunjukkan bahwa keraifan local masyarakat Using yang dapat dijadikan sumber belajar IPS dan relevan dengan kurikulum 2013 di Sekolah Dasar adalah kearifan lokal konservasi air, bidang pertanian, rumah adat, upaca adat, dan kesenian. Masyarakat Using menjunjung tinggi adat istiadat yang telah diwariskan secara turun temurun. Kearifan lokal tersebut dapat diintegrasikan dalam pembelajaran IPS di Sekolah Dasar pada jenjang kelas tinggi.